2017
DOI: 10.18632/oncotarget.23033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dihydropyrimidine dehydrogenase single nucleotide polymorphisms on prognosis of breast cancer patients with chemotherapy

Abstract: Defining biomarkers that predict therapeutic effects and adverse events is a crucial mandate to guide patient selection for personalized cancer treatments. DPD (dihydropyrimidine dehydrogenase, encoded by DPYD gene) is the initial and rate-limiting enzyme of metabolic pathway of fluoropyrimidines, and fluoropyrimidines are common used drug therapies for breast cancer. Previous studies on DPYD polymorphism were mainly focused on its association with fluoropyrimidines toxicity. In our present study, 5 DPYD singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, the prognostic value of DPYD polymorphisms in breast cancer has been little studied. Fengxia Qin et al in their work concidered the assosiation between SNPD DPYD and the effect of therapy based on regimens containing taxanes and anthracyclines (TA) [32]. The authors found that patients with non-wild type DPYD carriers treated with the TA regimen had a longer overall survival compared with "wild type" carriers who did not receive this treatment regimen.…”
Section: Methodsmentioning
confidence: 99%
“…However, the prognostic value of DPYD polymorphisms in breast cancer has been little studied. Fengxia Qin et al in their work concidered the assosiation between SNPD DPYD and the effect of therapy based on regimens containing taxanes and anthracyclines (TA) [32]. The authors found that patients with non-wild type DPYD carriers treated with the TA regimen had a longer overall survival compared with "wild type" carriers who did not receive this treatment regimen.…”
Section: Methodsmentioning
confidence: 99%
“…Of the three metabolic enzymes, DPYD is the most studied gene. More than 500 DPYD polymorphisms to date have been identified and have been linked to FP-related toxicity in cancer patients [22,[37][38][39][40][41][42][43][44][45]. Several of these variants are known to alter amino acid sequence or mRNA splicing, resulting in decreased enzymatic activity.…”
Section: Dihydropyrimidine Dehydrogenase (Dpd)mentioning
confidence: 99%
“…While some studies assessed a role of low DPD expression as a predictive factor for chemosensitivity [94] and for DFS in adjuvant setting [95] , other ones did not found a significant difference between high and low DPD groups in terms of DFS in adjuvantly treated patients [96,97] and OS in metastatic ones [98] . A recent study conducted by Qin et al [99] was the first aimed to investigate the prognostic role of DPYD polymorphisms in breast cancer. They demonstrated that DPYD c.1627A>G AG/GG polymorphism, detected from tumor tissue, was associated with poor OS and PFS in non-luminal patients treated with fluoropyrimidine-based chemotherapy [99] .…”
Section: Other Cancer Typesmentioning
confidence: 99%
“…A recent study conducted by Qin et al . [ 99 ] was the first aimed to investigate the prognostic role of DPYD polymorphisms in breast cancer. They demonstrated that DPYD c.1627A>G AG/GG polymorphism, detected from tumor tissue, was associated with poor OS and PFS in non-luminal patients treated with fluoropyrimidine-based chemotherapy [ 99 ] .…”
Section: Impact Of Dpd Expression In Different Cancer Typesmentioning
confidence: 99%